Benthic infaunal assemblages adjacent to an ocean outfall in Australian marine waters: Impact assessment and identification of indicator taxa. (January 2022) - Andrew-Priestley, Megan; Newton, Katie; Platell, Margaret E.; Le Strange, Lisa; Houridis, Harry; Stat, Michael; Yu, Richard Man Kit; Evans, Craig; Rogers, Zoe; Pallot, Jason; Van Den Broek, Jaman; MacFarlane, Geoff R.
Abstract: An impact assessment of oceanic effluent releases from Belmont wastewater treatment works (WWTW) in Newcastle, Australia, was undertaken. Benthic infaunal assemblages in sandy sediments of ~25 m water depth were examined, at sites adjacent to the release point, and at increasing distances up to 2 km in both a NE and SW direction over five consecutive years (2016–2020). Localised impacts were evident for infaunal assemblages, with sites within 20 m of the outfall ("Impact" site types) exhibiting lower taxa richness and Shannon diversity, higher abundances of polychaetes and/or nematodes, higher polychaete ratios, and shifts in assemblage composition in comparison to sites at greater distances during some years. Taxa with increased localised abundances at the outfall were identified as indicators for monitoring impacts, including deposit-feeding polychaetes (Families Polygordiidae, Paraonidae and Dorvilleidae) and Phylum Nematoda. Future infaunal monitoring could include molecular tools and paired sediment analyses. Highlights: Identification of localised impact zone from offshore ocean outfall using benthic infauna Medium-term infauna monitoring dataset for an Australian offshore location Site-specific tolerant, opportunistic and/or sensitive infauna indicator taxa Morphotaxonomic baseline for exploration of molecular and paired sediment analyses